A BRAF V600E Mutation in RET-Negative Medullary Thyroid Cancer. (10th March 2020) - Robbins, Richard J.; Thomas, Jessica S.; Osuna, Patricia Mejia; Shakil, Jawairia
Abstract : We report the case of a woman with a sporadic medullary thyroid carcinoma. Genomic analysis found that her tumor did not contain any common RET mutations but did harbor a BRAF V600E mutation. Only one other well-confirmed example of the BRAF V600E mutation has been reported in an MTC patient. We conclude that this common BRAF mutation may independently drive neoplastic transformation of human parafollicular C cells.